Analysis of Teaching Materials Needs for Digital Module Development in Physics Learning: Teachers Perception - Putri Dwi Sundari; Hidayati; Defrizal Saputra; Silvi Yulia Sari; Elarismoy Beporta Anusba (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to describe teachers’ needs for developing teaching materials. Concept understanding is important for students so that teaching materials are needed to improve students’ concept understanding. The type of research carried out is descriptive research with a quantitative and qualitative approaches. The data instruments are in the form of interview sheets and teacher needs analysis questionnaires. Questionnaires to find out the learning resources used by teachers, obstacles when learning physics, and learning resources needed by teachers to facilitate students. A total of nine physics teachers in high schools throughout the city of Padang were involved in this research. Based on the result data of analysis, it was found that 83% of teachers used printed teaching materials in learning. As many as 36% of teachers use teaching materials that they make themselves. As many as 86% of teachers have never used digital teaching materials, teachers are not sufficient as learning resources. As many as 83% supported the development of teaching materials on physics to improve students' understanding of concepts. It is hoped that the results of this research will become the basis for developing digital modules based on the POE model to improve understanding of concepts in kinematics.